University students´ perception of exposure to various English accents and their production - William Charpentier-Jiménez (Universidad de Costa Rica, 2019)
This article presents students' perception of English accent varieties in a BA in English and a BA in English Teaching. The purpose of this study was to find out higher education students' opinions on the incorporation of further English accents in their major. Until now, this topic has not been deeply studied in the Costa Rican context.  Results were obtained from a 16-point survey answered by 77 participants. Based on these results, the writer explains that a need to include a variety of native and non-native English accents exists and that a language program would benefit from it. The results demonstrate that 76.6% of students consider being able to imitate several types of English accents important, while 93.5% believe that what is important is being able to recognize and understand several accents. Data show that the majority of students consider the incorporation of various types of accents in their major essential. In practical terms, these results should promote a curricular change where several types of English accents should be incorporated.